2017
DOI: 10.1175/jamc-d-16-0384.1
|View full text |Cite
|
Sign up to set email alerts
|

The Mean and Turbulent Properties of a Wildfire Convective Plume

Abstract: The time-mean and time-varying smoke and velocity structure of a wildfire convective plume is examined using a high-resolution scanning Doppler lidar. The mean plume is shown to exhibit the archetypal form of a bent-over plume in a crosswind, matching the well-established Briggs plume-rise equation. The plume cross section is approximately Gaussian and the plume radius increases linearly with height, consistent with plume-rise theory. The Briggs plume-rise equation is subsequently inverted to estimate the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
5
40
0
Order By: Relevance
“…The largest simulated downward motion occurs in the upper plume behind the fire front (maximum of −7 m s −1 ), consistent with previous observations [47] and simulations [48]. (Figure 10d), which fall within the range of sensible heat fluxes as reported by [49]. They induce maxima of the 2-m temperature difference over the active fire area up to 70 K (Figure 10c).…”
Section: Dynamical Plume Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…The largest simulated downward motion occurs in the upper plume behind the fire front (maximum of −7 m s −1 ), consistent with previous observations [47] and simulations [48]. (Figure 10d), which fall within the range of sensible heat fluxes as reported by [49]. They induce maxima of the 2-m temperature difference over the active fire area up to 70 K (Figure 10c).…”
Section: Dynamical Plume Structuresupporting
confidence: 90%
“…However, above in the plume, the dynamics mainly controls the TKE production, probably partly due to the initial shear environment and partly due to the shear induced by the updraft itself. In agreement with observational studies [47,49], the simulation shows increases in both horizontal and vertical velocity variances at the fire front and above, up to a 5000-m height ( Figure 13). Simulated values are in the same order of magnitude as the LiDAR observation of [49] reporting maximum variance values from 7 to 14 m 2 s −2 in a plume overshooting with comparable height.…”
Section: Dynamical Plume Structuresupporting
confidence: 88%
See 1 more Smart Citation
“…This type of deep convective cloud is unique in its microphysical structure for the following reasons: (1) There exist high concentrations of small cloud droplets that result from a large number of cloud condensation nuclei due to the aerosol particles emitted by fire that compete for limited condensable water vapor (Andreae et al, ), and (2) these clouds initiate and develop under the vigorous dynamics and thermodynamics induced by the fire itself. The buoyancy generated by the sensible heat of wildfires can produce very strong updrafts (Lareau & Clements, ; Tory et al, ), which can further enhance the aerosol activation at the cloud base by increasing the supersaturation (Kablick et al, ; Luderer et al, ; Trentmann et al, ). Note that pyroCb often produces severe weather events that include large hail (>25 mm), enhanced lightning activity, extreme low‐level winds, and in some cases even tornadoes (Fromm et al, ; Lareau et al, ; Rosenfeld et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heating from the fire produces buoyancy forces in the atmosphere and modifies near-surface winds, which can eventually increase the rate of fire spread and intensity. The buoyancy forces in a wildfire can increase the updraft by 1 to 2 orders of magnitude of an average thunderstorm (Lareau and Clements 2017). Using a scanning Doppler lidar and mobile radiosonde system during two large wildfires in northern California, Lareau and Clements (2016) found that compared with the ambient wind, the flow within the plume is characterized by much stronger velocities when outbound speeds exceeded 15 m·s -1 and the wind profiles showed significant shear over the lowest 2 km of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%